Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1057/biosoc.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

BRCA patients in Cuba, Greece and Germany: Comparative perspectives on public health, the state and the partial reproduction of ‘neoliberal’ subjects

Abstract: The relationship among genetic technologies, biosocial identity and patient subjectivity has been the focus of an increasing range of social science literature. Examining mainly European and North American contexts this work has demonstrated the variable configurations of genetic knowledge-practices and the diverse implications for at-risk individuals and populations. This article brings together ethnographic research on genomic medicine, public health and breast cancer in Cuba, Greece and Germany. Although ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
0
16
0
4
Order By: Relevance
“…While these dynamics are clearly somewhat different in Cuba and Brazil, there are some notable similarities in the way in which notions of genetic risk are displaced and reframed. While studies in Europe and North America have also shown that genetic technologies and knowledge may not lead directly to the molecularisation of bodies (Gibbon, Kampriani, Zur Nieden, 2010;Lock, 2008), the findings presented here raise questions about the assumed pathways and consequences of biomedicalisation linked to the expansion of novel fields of healthcare such as genomics. While notions of bodily porosity or plasticity do seem to be more prominent in certain regions of South America (Sanabria, forthcoming), the relevance of a seemingly "Lamarckian" understanding of disease risk (genetic or otherwise) may also potentially be much more widespread, yet still perhaps somewhat under-examined not only in this region but also beyond.…”
Section: Patient-citizens and (De)molecularised Bodiesmentioning
confidence: 73%
“…While these dynamics are clearly somewhat different in Cuba and Brazil, there are some notable similarities in the way in which notions of genetic risk are displaced and reframed. While studies in Europe and North America have also shown that genetic technologies and knowledge may not lead directly to the molecularisation of bodies (Gibbon, Kampriani, Zur Nieden, 2010;Lock, 2008), the findings presented here raise questions about the assumed pathways and consequences of biomedicalisation linked to the expansion of novel fields of healthcare such as genomics. While notions of bodily porosity or plasticity do seem to be more prominent in certain regions of South America (Sanabria, forthcoming), the relevance of a seemingly "Lamarckian" understanding of disease risk (genetic or otherwise) may also potentially be much more widespread, yet still perhaps somewhat under-examined not only in this region but also beyond.…”
Section: Patient-citizens and (De)molecularised Bodiesmentioning
confidence: 73%
“…This paper has drawn on illustrative examples relating to the perceived causative effect of physical blows to the breast and gendered ideas about excessive and what is understood as ‘unnatural’ physical activity undertaken by women. While further research and analysis of the large and diverse data set will further illuminate this finding, the data presented here highlights the need to examine the varieties of biosocial identities that are at stake in the translation of genomic technologies across a diverse national and transnational global terrain (Gibbon et al., 2010). The final section of the paper points to a further difficulty linked to the effort to incorporate predictive medicine, that somewhat conflicts and would appear to be at odds with the institutional culture of family medicine in Cuba.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast to comparable research undertaken with clinical and non-clinical populations in the UK (see for instance Gibbon, 2007a) the meaning of ‘breast cancer risk’, as well as the morality normally associated with ‘health awareness’ and engagement in preventative health interventions, appeared to be somewhat differently articulated (see also Gibbon, 2009 and Gibbon et al., 2010 for further discussion of this contrast). Here two specific aspects of Cuban women’s health beliefs about the causes of breast cancer are examined.…”
Section: Public Health Family Doctors and Community Geneticsmentioning
confidence: 80%
See 1 more Smart Citation
“…A growing number of STS authors describe the important role that culturally entrenched routines, practices and ways of reasoning play in how people relate to science and technology in general (for example, Hecht, 2001;Jasanoff, 2005) and biomedicine and genetic testing in particular (for example, Felt et al, 2008Felt et al, , 2010Gibbon et al, 2010): people do not simply embrace or refuse genetic testing; rather, they engage in complex negotiations that include different experiences with science and technology, historically grounded visions of governance and politics, and culturally entrenched ideas of health, illness and the bodily self. In their comparative study of how people come to terms with two different biomedical technologies (organ transplantation and post-natal genetic testing) in France, the Netherlands and Austria, Felt et al (2010) have shown that by offering shared discursive resources and broader sociotechnical imaginaries (Jasanoff and Kim, 2009) different national technopolitical cultures matter deeply.…”
Section: Technopolitical Cultures: Recontextualising the Genetic Testmentioning
confidence: 99%